EFFECT OF ASPHALT CONTENT ON THE SURFACE TEXTURE OF ASPHALT CONCRETE-WEARING COURSE (AC-WC) MIXTURE - Meutia Regita Cahyani; Eti Sulandari; Slamet Widodo (Universitas Udayana, 2025)
Road preservation is carried out as an effort to improve road quality, evaluated through surface roughness levels, considering that adequate road texture is a crucial factor in ensuring rider safety and comfort. This study aims to analyze the relationship between variations in asphalt content and the Mean Texture Depth (MTD) value in asphalt mixtures. Surface roughness measurements obtained through the Sand Patch Method are expressed as MTD values representing average texture depth. Results for asphalt contents of 5%, 5.5%, 6%, 6.5%, and 7% yielded MTD values of 0.59 mm, 0.54 mm, 0.48 mm, 0.36 mm, and 0.26 mm for the upper side; 0.45 mm, 0.48 mm, 0.41 mm, 0.32 mm, and 0.24 mm for the lower side; and 0.52 mm, 0.51 mm, 0.45 mm, 0.34 mm, and 0.25 mm for the combined upper-lower sides. The relationship between MTD and asphalt content was analyzed using linear regression with the coefficient of determination (R²) as the evaluation parameter. Asphalt content influenced texture depth by 66.34% (upper side), 47.3% (lower side), and 53.73% (combined sides). The Voids Filled with Bitumen (VFB) parameter significantly contributed to MTD variation, with influence levels of 41.3% (upper), 46.07% (lower), and 43.13% (combined). The analysis demonstrates that lower asphalt content produces rougher asphalt mixture surface textures. AC-WC mixture testing confirms that asphalt content affects MTD values.